2014
DOI: 10.3174/ajnr.a4016
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Hemodynamic Risk Factors in Ruptured Aneurysms Imaged before and after Rupture

Abstract: BACKGROUND AND PURPOSE:Due to limited information about aneurysm natural history, choosing the appropriate management strategy for an unruptured aneurysm is challenging. By comparing unruptured and ruptured cases, studies have identified a variety of aneurysm morphologic and hemodynamic properties as risk factors for rupture. In this study, we investigated changes in 4 ruptured aneurysms before and after rupture and tested whether previously published risk factors identified a risk before rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…Baker et al (5) showed that elevated serum elastase levels were found in patients with both ruptured and unruptured aneurysms with an underlying increased serum elastase-alpha-1 antitrypsin ratio in these patients compared to normal controls. Non-invasive imaging evaluation of aneurysm surface ratios, non-sphericity, and pulsatility indices were also found to be consistent predictive risk factors of rupture up to years before the event in a small patient series (6). A role of smooth muscle cells in the formation, degeneration, and rupture of intracranial aneurysms has also been described (7).…”
Section: Introductionmentioning
confidence: 79%
“…Baker et al (5) showed that elevated serum elastase levels were found in patients with both ruptured and unruptured aneurysms with an underlying increased serum elastase-alpha-1 antitrypsin ratio in these patients compared to normal controls. Non-invasive imaging evaluation of aneurysm surface ratios, non-sphericity, and pulsatility indices were also found to be consistent predictive risk factors of rupture up to years before the event in a small patient series (6). A role of smooth muscle cells in the formation, degeneration, and rupture of intracranial aneurysms has also been described (7).…”
Section: Introductionmentioning
confidence: 79%
“…BNR is defined as the quotient between the MA body width and the caliber of the feeding/draining vessels (see Figure 3 ). Chien et al employed a similar measure to characterize arterial brain aneurysms and found a trend for increases in this index when comparing aneurysms before and after rupture (Chien and Sayre, 2014 ). BNR is computed based on the skeleton/radii analysis described in section MA Segmentation and Skeletonisation.…”
Section: Methodsmentioning
confidence: 99%
“…Comparable approaches have been extensively used for the characterization of larger scale vascular lesions, such as intracranial aneurysms (IA) (Dhar et al, 2008 ; Chien et al, 2011 ). Morphological parameters, such as aneurysm aspect ratio and non-sphericity index (Chien and Sayre, 2014 ) have been identified as risk factors for rupture of IA. Perfusion parameters, such as velocity, wall shear stress (Tarbell, 2010 ), and shear rate have been proposed to study IA progression and resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Традиционно рост и развитие интракраниальных А связывают с дегенеративными процессами сосудистой стенки в сочетании со сложным взаимодействием местных биологических и гемодинамических механизмов [6]. К факторам риска их разрыва относят размеры, форму аневризматического мешка, количественные показатели соотношений анатомических элементов А, локализацию и угол отхождения от несущего сосуда [1,2,13] а б вание такого высокоточного метода диагностики, как КТангиография интракраниальных артерий с последующей 2D и 3D реконструкцией изображений позволяет определять основные морфологические параметры А и вычислять индексы аневризмы, несущей артерии, несферичности, объема и поверхности аневризматического мешка [13]. Однако, хотя для каждого из упомянутых индексов определены граничные значения, ни один из них не отражает достоверно риск разрыва аневризмы.…”
Section: Discussionunclassified